Uji Daya Antelmintik Ekstrak Perasan dan Infusa Daun Srikaya (Annona squamosa L.) Terhadap Cacing Gelang Ayam (Ascaridia galli) Secara In Vitro - Susi Endrawati; Wiyana A. Saputri (Jurusan Biologi FMIPA Universitas Cenderawasih, 2015)
Srikaya (Annona squamosa L.) is a fruit that has been widely known to the people of Indonesia that have effective properties as traditional medicine. Srikaya seeds and leaves are known as a medicinal plant worm exterminator. This study aims to determine the anthelmintic influence of extract juice and srikaya leaf infused against roundworm of chicken in vitro, to determine the effect of concentration of extract juice and infuse of the srikaya leaf to the time of death of roundworm of chicken in vitro and to determine the most effective concentration of the extract juice and infuse of the srikaya leaf that has anthelmintic influence. This research is an experimental research design with Post test only controlled group design consisting of 150 of A. galli worms and were divided into 4 groups of treatments. Group 1 were put in NaCl 0.9 % liquid; group 2 was in srikaya leaves juice extract at a concentration of 25, 50, and 75 g/100 ml; group 3 was in srikaya leaves infuse with a concentration of 25, 50, and 75 g/100 ml, and group 4 was given 0.5 % pyrantel pamoate liquid. Each treatments containing 5 worms in 25 ml were done at 3 replication and incubated at 37 oC. The data were obtained from the observation of A. galli time of death every 15 minutes. The data were analyzed using One Way Anova test followed by the Post Hoc LSD test. There was an increasing of the death of A. galli correlating with the increase of the juice extract and infuse the srikaya leaf concentrations. The result showed there was a significant difference of NaCl 0.9 % and pyrantel pamoate 0.5 % treatments and there was no significant difference of the juice extract and infuse the srikaya leaf on worm death time. Extract juice and srikaya leaf infusion has anthelmintic influence against A. galli in vitro. The greater the concentration of the treatments, the greater anthelmintic influence visible on the death time acceleration of A. galli. Concentration of 75 g/100 ml is the most effective treatments of extract juice and srikaya leaf infusion but still lower than that of 0.4 % pyrantel pamoate.Key words: srikaya, A. squamosa, anthelmintic influence and A. galli